AWARENESS AND USE OF ACADEMIC SOCIAL NETWORKING SITES AMONG RESEARCH SCHOLARS OF STATE UNIVERSITY OF MAHARASHTRA IN THE SUBJECT OF LIBRARY AND INFORMATION SCIENCE: A STUDY - Kamble, Balaji A. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study investigated the awareness and use of academic social networking sites among research scholars. In the digital age, academic social networking sites (ASNS) have emerged as powerful tools for researchers to connect, collaborate, and disseminate their work. These platforms provide opportunities for scholars to interact with peers, share research findings, and build professional networks. This case study investigates the awareness and use of ASNS among research scholars of Library Science. Survey method were conducted through questionnaire tool used to collect the data from research scholars of ISEC Library and analysed using different parameter. The studies found that majority of the students were aware of ASNS and use this site for academic purpose. Further it alsodiscussed device used and impact of ASNS.